Yeast and fruit fly mutual niche construction and antagonism against mould. (15th April 2022) - Chakraborty, Amrita; Mori, Boyd; Rehermann, Guillermo; Hernández Garcia, Armando; Lemmen‐Lechelt, Joelle; Hagman, Arne; Khalil, Sammar; Håkansson, Sebastian; Witzgall, Peter; Becher, Paul G.
Abstract: A goal in insect–microbe ecology is to understand the mechanisms regulating species associations and mutualistic interactions. The spotted wing drosophila Drosophila suzukii develops in ripening fruit, unlike other drosophilids that typically feed on overripe fruit, and is associated with the yeast Hanseniaspora uvarum . We hypothesized that D. suzukii and H. uvarum engage in niche construction leading to a mutualistic relation, facilitating the exploitation of fruit and berries as larval substrate. We show that H. uvarum proliferates on both ripe and on unripe raspberries, mediates attraction of D. suzukii larvae and adult flies, enhances egg‐laying in mated females and is a sufficient food substrate to support larval development. Moreover, H. uvarum suppresses the antagonistic grey mould, Botrytis cinerea in collaboration with D . suzukii larvae, and produces less ethanol than baker's yeast. H. uvarum thus creates favourable conditions for D. suzukii larval development, which is susceptible to ethanol and grey mould. D. suzukii, on the other hand, vectors H. uvarum to suitable substrates such as raspberries, where larval feeding activity enhances growth of H. uvarum . Larval feeding also helps to suppress B. cinerea, which otherwise outcompetes H. uvarum on raspberry, in the absence of fly larvae. In conclusion, H. uvarum enhances D. suzukii larval development on unripe berries, and D. suzukii promotes H. uvarum dispersal and growth on berries. Yeast and fly modify their shared habitat in reciprocal niche construction and mutual interaction. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.